Tradisi Ibu Hamil Bersembunyi di Bawah Ranjang saat Gerhana Bulan: Studi Living Hadis pada Masyarakat Muslim - Elan Herlangga; Muhammad Alif (Jurnal Budi Pekerti Agama Islam, 2026)
The tradition of pregnant women hiding under the bed during a lunar eclipse is still found in some Muslim communities in Indonesia. This tradition is believed to serve as a means of protecting the fetus from the negative impacts of the eclipse, both physically and metaphysically. This study aims to examine this tradition from the perspective of Living Hadith, namely how the Prophet’s hadiths are understood, interpreted, and practiced within the social life of the community. This research employs a qualitative approach using field study methods, including observation, in-depth interviews, and documentation. The findings indicate that this tradition has no direct textual basis in the Prophet’s hadiths; rather, it has developed through processes of religious interpretation, local myths, and traditional knowledge that are associated with Islamic teachings. The community often relates this tradition to hadiths concerning eclipses as signs of God’s power and as moments to increase supplication and prayer. This tradition reflects a form of acculturation between Islamic values and local culture, while also demonstrating how hadiths are “lived” within the collective consciousness of the Muslim community, even when such practices do not fully align with the textual meanings of the hadiths.